Prevalencia de algunos componentes del síndrome metabólico en escolares y adolescentes con sobrepeso y obesidad. Hallazgos del estudio de factores de riesgo para enfermedad cardiovascular en escolares y adolescentes (2007)
ABSTRACT: Increasing prevalence of overweight and obesity in children and adolescents increases the risk of metabolic syndrome. Objective: to describe the prevalence of several components of metabolic syndrome in children and adolescents with overweight and obesity as compared with a control group. Methodology: It was a cross-sectional descriptive study derived from the study “Factores de riesgo cardiovascular en escolares y adolescentes de la ciudad de Medellín, Colombia, 2003”. As components of the metabolic syndrome were considered: triglycerides ≥110 mg/dL, cHDL ≤40 mg/dL, pre-prandial glucose ≥100 mg/dL, and arterial blood pressure ≥ percentile 90 (mm Hg). Results: The final sample included three groups: 121 obese, 240 overweighted and 361 people as control. Triglycerides as well as systolic and diastolic blood pressure were significantly lower in control group than the others, while cHDL was significantly higher in this group compared with the others. Prevalence of presence of at least one of the component of the metabolic syndrome showed a positive trend with regard to the Body Mass Index, consequently, children and adolescents obese had a higher prevalence of at least three or more components of metabolic syndrome. Conclusion: overweight and obesity are associated with a higher prevalence of metabolic syndrome. However, children and adolescents with normal Body Mass Index showed to have both risk factors and alteration of some components of metabolic syndrome rendering them more susceptible to develop the syndrome.